HUBUNGAN HASIL BELAJAR PER KELOMPOK MATA KULIAH DENGAN NILAI PLK MAHASISWA PROGRAM STUDI PENDIDIKAN SENI RUPA FBS UNP PADANG - Yulivia Bernia, Eswendi, Yofita Sandra (Serupa The Journal of Art Education, 2013)
The purpose of this research is to find out the correlation the  result of study in lesson group and the score of art training (PLK) teacher FBS UNP Padang. This is correlation research which aims to find out the correlation between free variable with bound variable. Free variable is the result of group study of art students lecturing subject which and bound variable is PLK. The finding showed that there is significant correlation in degree 5% between study result of each group of (1) Mata Kuliah Keahlian Berkarya (MKB), (2) Mata Kuliah Keilmuan dan Keterampilan, (3) Mata Kuliah  Pengembangan Kepribadian (MPK), (4) Mata Kuliah Prilaku  Berkarya (MPB) with students PLK value and there is no significant correlation toward study result of (5) Mata Kuliah Berkehidupan Bersama (MBB) with students PLK value.